2017
DOI: 10.1186/s40621-017-0105-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of marijuana and alcohol on fatal motor vehicle crash risk: a case–control study

Abstract: BackgroundConcurrent use of marijuana and alcohol in drivers is of increasing concern but its role in crash causation has not been well understood.Methods Using a case–control design, we assessed the individual and joint effects of marijuana and alcohol use on fatal crash risk. Cases (n = 1944) were drivers fatally injured in motor vehicle crashes in the United States at specific times in 2006, 2007 and 2008. Controls (n = 7719) were drivers who participated in the 2007 National Roadside Survey of Alcohol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 65 publications
2
31
1
1
Order By: Relevance
“…Simultaneous alcohol and marijuana (SAM) use can have more serious negative consequences than using either substance alone (for a review, see Yurasek et al., ). These include driving under the influence and having alcohol‐related accidents (Arterberry et al., ; Chihuri et al., ; Lipperman‐Kreda et al., ; Terry‐McElrath et al., ), cognitive impairment (Mallett et al., ), and substance use disorder symptomatology (Agrawal et al., ; Mallett et al., ; Midanik et al., ; Subbaraman and Kerr, ). The majority of individuals who use alcohol and marijuana engage in SAM use on at least some occasions (Agrawal et al., ; Brière et al., ; Collins et al., ; Midanik et al., ; Pape et al., ; Subbaraman and Kerr, ).…”
Section: Normative Influences On Substance Usementioning
confidence: 99%
“…Simultaneous alcohol and marijuana (SAM) use can have more serious negative consequences than using either substance alone (for a review, see Yurasek et al., ). These include driving under the influence and having alcohol‐related accidents (Arterberry et al., ; Chihuri et al., ; Lipperman‐Kreda et al., ; Terry‐McElrath et al., ), cognitive impairment (Mallett et al., ), and substance use disorder symptomatology (Agrawal et al., ; Mallett et al., ; Midanik et al., ; Subbaraman and Kerr, ). The majority of individuals who use alcohol and marijuana engage in SAM use on at least some occasions (Agrawal et al., ; Brière et al., ; Collins et al., ; Midanik et al., ; Pape et al., ; Subbaraman and Kerr, ).…”
Section: Normative Influences On Substance Usementioning
confidence: 99%
“…1 Further, studies have shown that marijuana use among adolescents is associated with increased risk for depression and anxiety disorders, chronic bronchitis and respiratory infections and deadly motor vehicle crashes. [14][15][16] Alcohol is both a legal and socially accepted substance in Jamaica. The social acceptability of this substance results in the public often ignoring its health risks.…”
Section: Discussionmentioning
confidence: 99%
“…First, we find nearly half of first-time DUI offenders who continue to use alcohol also report the past-month use of marijuana. Given evidence that combined use of marijuana and alcohol while driving increases crash risk (Bramness et al, 2010; Chihuri et al, 2017; Li et al, 2017) and that co-occurring drug use is positively associated with DUI recidivism (Mullen et al, 2015; Nochajski and Stasiewicz, 2006), our findings of significantly lower DUI avoidance self-efficacy among AM co-users suggest that methods to screen and identify AM co-use at DUI program intake may be warranted. Given the expansion of marijuana legalization policies, and the rise in public health and regulatory concerns about how to detect, prevent, and intervene in incidents of marijuana-impaired driving (Davis et al, 2016; Huestis, 2015; Pacula et al, 2014; Watson and Mann, 2016), monitoring rates of AM co-use and its effects may help inform future policy.…”
Section: Discussionmentioning
confidence: 83%
“…There is growing concern over the co-use of alcohol and marijuana (AM) because their combined effects on psychomotor and cognitive functions have additive or possibly synergistic effects on impairment (Dubois et al, 2015; Hartman et al, 2015; Ramaekers et al, 2000; Ronen et al, 2010; Sewell et al, 2009), significantly increasing crash risk compared to the use of either substance alone (Bramness et al, 2010; Chihuri et al, 2017; Li et al, 2017; Ramaekers et al, 2000). These effects underscore the importance of evaluating the prevalence of co-use among those who drive while under the influence, as well as the extent to which the underlying cognitive or behavioral risk factors contribute to these associations.…”
Section: Introductionmentioning
confidence: 99%